Aging Prisoners in Switzerland: An analysis of Their Health Care Utilization. (April 2016) - Wangmo, Tenzin; Meyer, Andrea H.; Handtke, Violet; Bretschneider, Wiebke; Page, Julie; Sommer, Jens; Stuckelberger, Astrid; Aebi, Marcelo F.; Elger, Bernice S.
Objective: This study assessed health care utilization of aging prisoners and compared it with that of younger prisoners.Method: Health care utilization comprised visits to general practitioners (GPs), nurses, and mental health professionals (MHPs) for a period of 6 months. Using retrospective study design, data were extracted from medical records of 190 older prisoners (50 years and older) and 190 younger inmates (18-49 years). Age group was a dichotomous predictor variable with type of sentencing and time spent in prison as covariates. Descriptive statistics and generalized linear mixed models (GLMMs) were performed.Results: For each of the three outcome variables, two GLMMs were constructed. The first model only included age group as the predictor variable (3 × Unadjusted models). The second included the two covariates in addition to the predictor variable (3 × Adjusted model). Results from the adjusted model indicate that visits to GPs significantly differed between the two age groups ( p = .022). Older prisoners visited GPs 1.43 times more often than younger prisoners over the 6-month period (adjusted risk ratio [RR] = 1.43, 95% confidence interval [CI] = [1.05, 1.94]). The finding for visits to nurses was not statistically significant ( p = .080). However, older prisoners visited nurses 1.36 times more frequently (adjusted RR = 1.36, 95% CI = [0.96, 1.91]). Finally, older prisoners visited MHPs 1.24 times more often than younger prisoners (adjusted RR = 1.24, 95% CI = [.95, 1.61]) and this finding was also not statistically significant ( p = .11).Discussion: Study findings underline that older prisoners utilized health care more often than younger prisoners although in most models the finding did not reach statistical significance. The prison system must develop solutions to address the needs of an aging population, particularly those with physical and mental health problems.